2020
DOI: 10.1016/j.shaw.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Do Low Self-Esteem and High Stress Lead to Burnout Among Health-Care Workers? Evidence From a Tertiary Hospital in Bangalore, India

Abstract: Background Low self-esteem can be an issue among health-care workers due to the hierarchical medical system. Health-care workers are also in a high pressure environment that can lead to stress and burnout. This study was conducted to estimate the proportion of health-care workers with low self-esteem, high stress, and burnout and the factors associated with these in a private hospital in Bangalore city. Methods This cross-sectional study included a random sample of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 16 publications
(13 reference statements)
7
30
1
8
Order By: Relevance
“…In addition to sociodemographic characteristics, several work-related factors were suggested to affect the stress levels of HCWs, including role conflict and ambiguity, self-esteem and social support [ 20 , 21 , 22 , 23 , 24 ]. Role conflict and ambiguity can be attributed to the absence of clear and reliable data about the activities needed in a specific position, the unpredictability of performance results and information deficiency regarding the required tasks [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sociodemographic characteristics, several work-related factors were suggested to affect the stress levels of HCWs, including role conflict and ambiguity, self-esteem and social support [ 20 , 21 , 22 , 23 , 24 ]. Role conflict and ambiguity can be attributed to the absence of clear and reliable data about the activities needed in a specific position, the unpredictability of performance results and information deficiency regarding the required tasks [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for doctors, Shanafelt et al [ 54 ] confirmed that doctors experience symptoms of burnout at significantly higher rates compared with doctoral-level professionals in other fields. Doctors interact with colleagues or patients every day, but the focus of communication is almost always on the disease development, leaving them little time and few tools to relieve stress [ 8 ]. As to the radiation work types, interventional radiology was the largest group with job burnout, followed by diagnostic radiology.…”
Section: Discussionmentioning
confidence: 99%
“…Medical radiation workers belong to a special occupational group that has dual roles as health care workers and radiation workers. Health care workers are among the most stressed professionals owing to their risk of infections, high job demands, dissatisfied patients, and intensely competitive promotions [ 8 , 9 ]. More than half of US physicians were found to have at least one symptom of burnout, which was significantly higher than in the general population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Identificou-se que a presença de autoestima mais elevada apresenta influência na presença de níveis mais baixos dos sintomas da Síndrome de Burnout (Leroy-Frémont;Desrumaux&Moundjiegout, 2014;Kang;Twigg&Hertzman, 2010). Assim, a baixa autoestima pode ser considerada preditora de Burnout (Johnson et al, 2020).…”
Section: Descrençaunclassified
“…Cabe destacar um fator limitante de 'causa x efeito' em relação à autoestima apontada na literatura. Há pesquisas que adotam o posicionamento da autoestima ser preditora (Johnson et al, 2020;Leroy-Frémont;Desrumaux&Moundjiegout, 2014;Kang;Twigg&Hertzman, 2010).Todavia,também há pesquisas que adotam o resultado na autoestima ser o efeito (Enache, 2013). Adotou-se nesta pesquisa a primeira perspectiva.…”
Section: Descrençaunclassified